THE ROLE OF ACCOUNTING KNOWLEDGE IN CONFRONTING CREATIVE ACCOUNTING PRACTICES: AN APPLIED STUDY OF THE IRAQI NATIONAL INSURANCE COMPANY (World Economics and Finance Bulletin, 2024)
This study aims to highlight the role of accounting knowledge in facing innovative accounting practices among a sample of employees in the Iraqi National Insurance Company. To indicate the level of importance of the variables of the study, both accounting knowledge and creative accounting were addressed, and the results of the study were analyzed based on the descriptive approach, and to achieve the objectives of the study and test its hypotheses, the questionnaire tool was used to collect the necessary data and information that show the importance of its variables. As (153) questionnaires were distributed to the employees of the company, and accordingly the statistical packages were used for each of (SPSS. V.29 & Excel.v.2016) to transcribe the analysis of the results, and this study found a correlation and impact between accounting knowledge in the face of creative accounting practices and this helps accounting knowledge to enhance its capabilities in the level of transparency in financial reporting processes, especially with regard to the financial and accounting reporting processes
Keywords: accounting knowledge; creative accounting; knowledge of accounting recognition